2014
DOI: 10.1021/jz402510a
|View full text |Cite
|
Sign up to set email alerts
|

Probing Local Structure of Layered Double Hydroxides with 1H Solid-State NMR Spectroscopy on Deuterated Samples

Abstract: By using a simple and efficient deuteration process, (2)H has been successfully introduced into layered double hydroxides (LDHs). Due to significantly less (1)H-(1)H homonuclear dipolar coupling, high-resolution (1)H solid-state NMR spectra can now be obtained conveniently at medium to low spinning speed to extract the information of cation ordering in LDHs. Furthermore, we show that double-resonance experiments can be applied easily to investigate internuclear proximities and test possible cation-ordered supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 36 publications
4
24
0
Order By: Relevance
“…The broad resonance at 4.9 ppm can then be tentatively assigned to hydroxyl groups in -Zn(OH) 2 . The large linewidth of the peak is associated with large 1 H-1 H homonuclear dipolar coupling in -Zn(OH) 2 , which is often observed in the spectra of metal hydroxides [40,41] and consistent with the presence of large spinning sideband manifolds (-Zn(OH) 2 in Figure 1c). Deuteration has often been used to dilute 1 H and increase the spectra resolution [41].…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…The broad resonance at 4.9 ppm can then be tentatively assigned to hydroxyl groups in -Zn(OH) 2 . The large linewidth of the peak is associated with large 1 H-1 H homonuclear dipolar coupling in -Zn(OH) 2 , which is often observed in the spectra of metal hydroxides [40,41] and consistent with the presence of large spinning sideband manifolds (-Zn(OH) 2 in Figure 1c). Deuteration has often been used to dilute 1 H and increase the spectra resolution [41].…”
Section: Resultssupporting
confidence: 69%
“…The large linewidth of the peak is associated with large 1 H-1 H homonuclear dipolar coupling in -Zn(OH) 2 , which is often observed in the spectra of metal hydroxides [40,41] and consistent with the presence of large spinning sideband manifolds (-Zn(OH) 2 in Figure 1c). Deuteration has often been used to dilute 1 H and increase the spectra resolution [41]. The FT-IR data of deuterated -Zn(OH) 2 ( Figure S4) as well as NMR spin counting results suggest D has been successfully introduced to Zn(OH) 2 (see additional discussion in the supporting information).…”
Section: Resultssupporting
confidence: 69%
“…There is evidence of M(III)-rich regions with Al-O-Al connectivities in MgAl LDH's, which has been reported from 1 H and 27 Al SSNMR, [7,8] but not observed by Sideris et al [6,[9][10][11]. It is of interest to see if similar Ga rich regions can be found in the MgGa LDH.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, the ordering of M(III) and M(II)/M(III) ratios can be determined if the -OH groups can be quantified. It has been demonstrated that solid-state NMR (SSNMR) provides this information and gave a detailed insight into local environment of the cation in magnesium aluminum (MgAl) LDH's [6][7][8][9][10][11], including the distribution of Al in the cation layer, the presence of structural defects -information which is very difficult determined with X-ray diffraction techniques, which rely on long range order. The dynamics and orientation of both inorganic and organic anions in the interlayer has been extensively studied by Kirkpatrick et al [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation